PLANNING AND CONTROLLING INVENTORY OF COAL USING MODEL PROBABILISTIC Q BACKORDER WITH CONSIDER OF STORAGE CAPACITY - Ekawati, Ratna (JEMIS (Journal of Engineering & Management in Industrial System), 2018)
Inventory of fuel is very important in the production process, because the fuel is one factor that ensures smooth production process. PT. XYZ is a company engaged in provision power and steam with the coal. On determining amount of the current inventory of coal in PT XYZ still fluctuating from storage capacity, so it is necessary to study the planning and controlling inventory of coal with consider of storage capacity. This study aims to optimize the amount of the coal fuel, determine reorder point, determine safety stock and determine total cost of inventory using inventory probabilistik Q model backorder storage capacity constrain. Data processing results obtained optimal order for each the coal is as much as 11.000 tons, Reorder point is as much as 607,346 tons, safety stock is as much as 1,292 tons and total cost of inventory is as much as Rp. 16.052.531.575 using inventory probabilistik Q model backorder storage capacity constrain.Â